Tilings with Congruent Edge Coronae - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2021)
In this paper, we discuss properties of a normal tiling of the Euclidean plane with congruent edge coronae. We prove that the congruence of the first edge coronae is enough to say that the tiling is isotoxal.